1992
DOI: 10.1152/jn.1992.67.3.738
|View full text |Cite
|
Sign up to set email alerts
|

GABAA receptor antagonist bicuculline alters response properties of posteroventral cochlear nucleus neurons

Abstract: 1. The role of GABAergic inhibitory inputs onto posteroventral cochlear nucleus (PVCN) neurons in the anesthetized chinchilla was investigated through iontophoretic application of the GABAA receptor agonist muscimol and the GABAA receptor antagonist bicuculline. The majority of the neurons studied displayed phasic temporal response patterns. 2. All the neurons were sensitive to bicuculline and displayed an increase in discharge rate, which was greatest during the post-onset portion of the response. Most of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…Moreover, there is some evidence that spectral integration in ACx is more extensive than in subcortical auditory regions. For example, whereas blockade of local inhibition in ACx expands frequency receptive Welds (see above), similar manipulations in the cochlear nucleus or inferior colliculus produce lesser or no expansion (Caspary et al, 1994;LeBeau et al, 2001;Palombi and Caspary, 1992). However, this result may only indicate that cortical and subcortical receptive Welds are not similarly regulated by inhibition; direct measurement of subthreshold receptive Welds at cortical and subcortical levels (in particular, at the thalamic level) will be needed to resolve this issue fully.…”
Section: What Is the Extent Of Spectral Integration In Acx Neurons?mentioning
confidence: 99%
“…Moreover, there is some evidence that spectral integration in ACx is more extensive than in subcortical auditory regions. For example, whereas blockade of local inhibition in ACx expands frequency receptive Welds (see above), similar manipulations in the cochlear nucleus or inferior colliculus produce lesser or no expansion (Caspary et al, 1994;LeBeau et al, 2001;Palombi and Caspary, 1992). However, this result may only indicate that cortical and subcortical receptive Welds are not similarly regulated by inhibition; direct measurement of subthreshold receptive Welds at cortical and subcortical levels (in particular, at the thalamic level) will be needed to resolve this issue fully.…”
Section: What Is the Extent Of Spectral Integration In Acx Neurons?mentioning
confidence: 99%
“…For example, Evans and Zhao (1993) have shown that side-band inhibition, important for spectral contrasts and dynamic range, is probably mediated by glycine in the DCN. Glycine affects the ongoing discharge rates within the excitatory response areas of many neuronal types in the ventral CN, including PVCN phasic-firing neurons and AVCN neurons with chopper and primarylike response patterns (Palombi and Caspary, 1992;Caspary et al, 1993Caspary et al, , 1994. This has been hypothesized to act either to control dynamic range and/or detection of signals in noise.…”
Section: Possible Roles Of Gaba and Glycine In The Cnmentioning
confidence: 99%
“…Intracellular recordings have shown inhibitory potentials in response to tones and auditory nerve stimulation Rhode 1987, 1989;Wickesberg and Oertel, 1990;Feng et al, 1994). Pharmacological manipulations also reveal ongoing inhibitory effects on the responses of cells in the CN (Palombi and Caspary, 1992;Caspary et al, 1993Caspary et al, , 1994. Inhibitory effects on some cell types in the dorsal cochlear nucleus (DCN) are evoked by contralateral acoustic stimulation (Young and Brownell, 1976).…”
mentioning
confidence: 99%
“…These include, but are not limited to, rate-level functions and aurality (Pollak and Park, 19931, interaural frequency-intensity disparities (Park and Pollak, 19931, frequency modulation (Mendelson, 1992), echo suppression (Wickesberg and Oertel, 19901, and disinhibition (Adams and Mugnaini, 1990), to name just a few. Not all aspects of receptive field fine structure, however, at least in the auditory hindbrain, are under GABAergic modulation (Palombi and Caspary, 1992). In other instances it has proved difficult to define precisely the interlaminar substrates for phenomena such as end inhibition, despite the readily demonstrable pathways that might subserve it (Grieve and Sillito, 1991).…”
Section: Spatial Distributionmentioning
confidence: 99%